The moderating effect of corporate governance to the relationship of corporate social responsibility and product market competition to company value - Marpaung, Elyzabet Indrawati; Augustine, Yvonne (Technium Social Sciences Journal, 2021)
The objective of this research is to find out the moderating effect of corporate governance on the relationship of corporate social responsibility and product market competition to company value. The control variable in this study is company size. The sample of this study was 216 observations consisting of 54 manufacturing companies listed in the Indonesia Stock Exchange from 2016 until 2019. Moreover, the simple random sampling method is employed to grab them. To analyze the data, we use the multiple regression model with polling data. The findings of this research are product market competition negatively affects company value. In opposition, corporate social responsibility and corporate governance positively affect company value. Meanwhile, corporate governance only moderates the effect of product market competition on the company value. The implication of this study is that good corporate governance practices can reduce the negative effects of PMC on company value.